Determination of criteria affecting the executive dashboard design to support decision making in port authorities. Issue 2 (30th January 2020) - Oguz, Mehmet; Keceli, Yavuz
Senior executives of a port authority spend most of their time by collecting information and making individual decisions via the collected information. They need customised decision support systems to support these decisions. It is necessary to develop executive dashboards specific to them although very few of them possess such dashboards. Hence, it is a necessity to determine the criteria needed to design such dashboards for an effective decision making. The purpose of this study is to determine the criteria needed to design executive dashboards for port executives so that they can make effective decisions. Within this scope, a target group study comprising of field experts was conducted, and the data obtained were analysed with the Delphi technique. Consequently, 61 criteria in total were determined in four different criterion groups.